Dikkat Eksikliği Hiperaktivite Bozukluğu Olan Çocukların Atopi ve Alerjik Hastalıklar Yönünden İncelenmesi - Akyol, Şule Turan (My University, 2009)
Dikkat Eksikliği Hiperaktivite Bozukluğu, dikkat eksikliği, hiperaktivite ve dürtüsellik ile karakterize çocukluk çağının sık görülen bir hastalığıdır. Çocukların %2-12'sini etkileyen genellikle genetik geçişli psikiyatrik bir bozukluktur. Alerjik rinit, egzema ve astımı kapsayan atopik hastalıklarda oldukça sık görülmektedir. Literatürde DEHB ve atopik hastalıklar arasındaki ilişkiyi araştıran çalışmalarda değişik sonuçlar bildirilmiştir. Araştırmalar DEHB tanılı hastalarda alerjik hastalıkların sık görüldüğü, DEHB ve alerjik hastalıkların ortak biyolojik nedene bağlı geliştiği ve bu biyolojik yolun beyin katakolaminleri olabileceği yönündedir. Bumunla birlikte karşıt görüşte çalışmalarda bulunmaktadır. Bu çalışmanın amacı doktor tanılı DEHB ile takip edilen hastalarda alerjik hastalıklar ve atopinin sık olup olmadığını araştırmaktırÇalışmamıza 2008-2009 yılları arasında çocuk psikiyatri polikliniğinde DSM IV tanı kriterlerine göre DEHB tanısı konulmuş 55 hasta alındı. Kontrol grubu olarak çevresel ve genetik farklılıkları en aza indirmek için DEHB tanısı ile izlenen hastaların kardeşleri ve genel populasyonu temsil etmek amacı ile 50 sağlıklı çocuk alındı. Astım, alerjik rinit, atopik dermatit sıklığı üç grup arasında karşılaştırıldı. Tüm çocuklar bir allergolog tarafından alerjik hastalıklar yönünden muayene edildi. Uluslararası Çocukluk Çağı Astım ve Alerji Çalışması (ISAAC) sorularının Türkçe modifikasyonu ailelerle yüz yüze görüşülerek uygulandı. Serum IgE düzeyi, en sık görülen altı allerjene karşı epidermal deri testi ve eozinofil sayısına bakıldı. Fizik muayenesinde alt hava yolu obstruktif bulguları saptanan ve koopere olabilen olgulara solunum fonksiyon testi (SFT) yapıldı. Total Ig E düzeyi ve alerjen duyarlılığı DEHB olan grupta istatistiksel olarak anlamlı yüksek bulundu (p< 0.05). Alerjik rinit sıklığı DEHB grubunda diğer iki gruba oranla istatistiksel olarak anlamlı yüksek bulundu. Astım DEHB grubunda kontrol II grubuna göre yüksek bulunurken kontrol I grubuyla karşılaştırıldığında istatistiksel olarak anlamlı fark yoktu. Atopik Dermatit açısından gruplar arasında fark saptanmadıSonuç olarak DEHB tanısı ile takip edilen hastalarda alerjik hastalıklar ve atopi kontrol I ve kontrol II gruplarına göre sık bulundu. Çocuk psikiyatri polikliniğinde DEHB tanısı ile izlenen hastaların alerjik hastalıklar yönünden değerlendirilmesi ve tespit edilen hastaların tedavisi yararlı olabilir.Anahtar Kelimeler: Alerjik Rinit, Astım, Atopik Dermatit, Dikkat Eksikliği, Hiperaktivite

Attention Deficit Hyperactivity Disorder (ADHD) is a common childhood problem characterized by a triad of difficulties with attention, hyperactivity and impulsivity. It is highly heritable psychiatric disorder that affects 2-12 % of children worldwide. Atopic disorders, which are generally agreed to encompass allergies, allergic rhinitis, eczema and asthma are even more common. There are mixed research results in the literature regarding a possible association between Attention Deficit Hyperactivity Disorder (ADHD) and atopic disorders. It has been suggested that children with attention deficit hyperactivity disorder are likely to show allergic disorders and that both ADHD and allergic disorders may share common biological background. Biological background may be assumed that may involve brain catecholamines. On the other hand, there are others that suggest the opposite. The purpose of this study is to determine whether allergic disorders and atopy are commen in a pediatri population with physician-diagnosed ADHDBetween 2008 and 2009, 160 children were included in our study and were divided into three groups. Group one was consist of 55 subjects (mean age ± years) who met Diagnostic and Statistical Manual of Mental Disorders, Fourth edition criteria for ADHD . Another 55 children (mean age ± years) were in group two who were also chosen among the group one's siblings as controls to minimize genetic and environment factors effects. Third group was included 50 healthy children. Prevalence of asthma, atopic dermatitis and allergic rhinitis were compared between three groups. Comprehensive examination was performed for all subjects by same pediatric allergist. Turkish version of International Study of Asthma and Allergies in Children (ISAAC) questionnaires were utilized for each subject. Face to face methodology was used complete all ISAAC questionnaires. In addition to this, total blood count for potential eosinophilia, total IgE levels were measured and skin prick tests were performed for each subjects. However, BFT (Breathing Function Test) were only performed for the subjects who had obstructive symptoms and also were cooperativeTotal IgE levels and sensitivity of allergens were significantly higher (p<0.05) in group one. Prevalence of allergic rhinitis symptoms were found to be significantly higher in ADHD group compared to the other groups (p<0.05). Asthma was found significantly higher in ADHD group compared to the third group however not significant from second group. Interestingly, we found no significant difference of prevalence for atopic dermatitis between three groupsOur study has highlighted that allergic disorders are higher in child who have had ADHD and its evaluation and treatment could benefit patients with ADHD.Key Words: allergic rhinitis, asthma, atopic dermatitis, attention deficit, hyperactivity
Evaluation of the Children with Attention Deficit Disorder with Respect to Presence of Atopy and Allergic Disease
Keywords: Çocuk Sağlığı ve Hastalıkları; Child Health and Diseases